SISTEM INFORMASI DATA KEPENDUDUKAN PADA KANTOR KECAMATAN CIMAHI UTARA - Hidayat, Atep (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2025)
Office District of Cimahi North represent one of the existing District is cimahi town, having four Sub-District. that is sub-district of Cibabat, Cipageran, Citeurep, Pasirkaliki. Frequent Problems appear in this Office District is in data processing like seeking and is depository of not regular data and less well guaranted its security. And also presentation of less available report. Is one of them caused by its process still done manually. Pursuant to existing problems hence developed a information system of data residental by using prototype method with model approach of Oriented Objeck ( OO) using OOA ( Object Orientied Analysis) and OOD ( Object Oriented Design). visualizinged with UML ( Unified Modelling Language). With made by Information System expected can give amenity especially to part of Division head Governance in the case of process data and provide residential information swiftly.